UJI AKTIVITAS ANTIOKSIDAN DARI AMPAS HASIL PENGOLAHAN SAGU (Metroxylon sagu Rottb) - Talapessy, Selvian; Suryanto, Edi; Yudistira, Adithya (PHARMACON, 2013)
ABSTRACT The study aimed to determine the phenolic content and antioxidant activity of sago waste processing results. Results of processing sago pulp esxtraction was conducted using 1 x 24 hour maceration using solvents ethanol with a concentration of 20, 40, 60 and 80%. Phenolic content was determined by Folin Ciocalteu method and determination of antioxidant activity using the DPPH free radical scavengers. The results showed that the extract with the solvent concentration of 40% has a higher total phenolic 83,26 Î¼g/mL followed by solvent extract concentration of 20, 60 and 80% respectively 70,01; 60,58; 22,04 Î¼g/mL. extract with 60% solvent concentration has free radical scavengers activity the highest of 82,75% followed by concentration of solvent extracts 80, 20 and 60% are respectively 80,45; 76,62; 62,83%. These results suggest that the processing of sago pulp extract contains phenolic antioxidants and can be potentially as. Keywords : pulp extract sago precessing results, phenolic compend, antioxidants.